Digital Supervision of Children as a Form of Modern Hadhanah in Islamic Law - Akhyar Akhyar (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2026)
The development of digital technology has changed the parenting patterns in Muslim families. Children not only interact in the physical environment, but also in the digital space that presents various opportunities and risks, such as exposure to negative content, cyberbullying, digital exploitation, and gadget addiction. This condition requires a reinterpretation of the concept of hadhanah in Islamic law to remain relevant to the challenges of the digital era. This study aims to analyze digital supervision of children as a form of modern hadhanah in Islamic law and examine its relevance in the perspective of maqāṣid al-syarī'ah. This research uses a normative legal research method with a qualitative approach through library research. Data were obtained from the Qur'an, hadith, jurisprudence, books, scientific journals, and literature related to Islamic family law, child protection, and digital parenting. Data analysis was carried out in a descriptive-analytical manner using a conceptual approach and the perspective of maqāṣid al-syarī'ah. Research shows that digital supervision is a form of developing hadhanah functions that include regulating the use of gadgets, assisting online activities, digital literacy education, and protecting children from various risks in cyberspace. Digital surveillance is also in line with the purpose of maqāṣid al-syarī'ah in safeguarding religion, soul, intellect, descendants, and children's property. Digital surveillance has a strong legitimacy in Islamic law as an instrument of child protection and can be constructed as a form of modern hadhanah that is adaptive to technological developments and contemporary parenting needs.